The Influence of Work Motivation, Work Discipline and Technology on Increasing Employee Performance at the Office of the Head of Aek Pamingke Plantation Village - Khairul Amsyah; Yudi Prayoga; Abdul Halim (Quantitative Economics and Management Studies, 2023)
The purpose of this study was to determine and analyze the influence of work motivation, work discipline, technology, and performance improvement at the Village Head's Office. The research method used in this study is a quantitative research method. This research also includes quantitative research that is correlational. The population in this study were all employees at the Village Head's Office with a total of 44 people. The number of samples used in this study amounted to 44 people. Where the entire population is used as a research sample using the saturated sample method. The data used in this study is primary data, namely data obtained directly by researchers from measuring the length of the short intervals in the measuring instrument is the Likert scale. The data analysis technique used in this study is a quantitative data analysis technique using statistical methods. This study uses the calculation results of the IBM Statistical Package For The Social Science (SPSS) version 26 which aims to determine the level of significance and the relationship between the independent variables and the dependent variable.